Nose-to-Brain Delivery by Nanosuspensions-Based in situ Gel for Breviscapine - Chen, Yingchong (Int J Nanomedicine, 2020)
PURPOSE: Nose-to-brain drug delivery is an effective approach for poorly soluble drugs to bypass the blood–brain barrier. A new drug intranasal delivery system, a nanosuspension-based in situ gel, was developed and evaluated to improve the solubility and bioavailability of the drug and to prolong its retention time in the nasal cavity. MATERIALS AND METHODS: Breviscapine (BRE) was chosen as the model drug. BRE nanosuspensions (BRE-NS) were converted into BRE nanosuspension powders (BRE-NP). A BRE nanosuspension in situ gelling system (BRE-NG) was prepared by mixing BRE-NP and 0.5% gellan gum (m/v). First, the BRE-NP were evaluated in terms of particle size and by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Subsequently, the critical ionic concentration of the gellan gum phase transition, influence of the deacetylated gellan gum (DGG) concentration on the expansion coefficient (S%), water-holding capacity, rheological properties and in vitro release behaviour of the BRE-NG were investigated. The pharmacokinetics and brain distribution of the BRE-NG after intranasal administration were compared with those of the intravenously injected BRE-NP nanosuspensions in rats. RESULTS: The rheology results demonstrated that BRE-NG was a non-Newtonian fluid with good spreadability and bioadhesion performance. Moreover, the absolute bioavailability estimated for BRE-NG after intranasal administration was 57.12%. The drug targeting efficiency (DTE%) of BRE in the cerebrum, cerebellum and olfactory bulb was 4006, 999 and 3290, respectively. The nose-to-brain direct transport percentage (DTP%) of the cerebrum, cerebellum and olfactory bulb was 0.975, 0.950 and 0.970, respectively. CONCLUSION: It was concluded that the in situ gel significantly increased the drug retention time at the administration site. Therefore, the nanosuspension-based in situ gel could be a convenient and effective intranasal formulation for the administration of BRE.